Grignard condensation routes to 1, 3‐disilacyclobutane‐containing cyclolinear polycarbosilanes. Issue 9 (15th February 2017) - Liu, Xinxing; Rathore, Jitendra S.; Dubois, Geraud; Interrante, Leonard V.
ABSTRACT: Alkylene‐ and arylene‐bridged cyclolinear polycarbosilanes (CLPCS) with 1, 3‐disilacyclobutane (DSCB) rings incorporated in the main chain of the polymer were prepared by polycondensation between corresponding di‐functional DSCB derivatives and di‐Grignard reagents. Well‐defined, low molecular weight ( M n  = 3–5K; DP = 17–26), hexylene‐ and phenylene‐bridged CLPCS polymers were obtained without appreciable ring opening of the DSCB rings. Large exothermic peaks were observed in the DSC for these CLPCSs, which indicated, along with the IR spectra, that crosslinking occurred on heating to about 250 °C via the ring opening of the embedded, alternating, DSCB rings. Moreover, PB‐CLPCS undergoes photochemically induced crosslinking on UV irradiation to form crosslinked polycarbosilane network films. The spin‐cast, cured, films of these CLPCSs exhibit relatively low dielectric constants and promising thermal and mechanical properties for applications in electronics, for example, directly UV‐photoimprinted low‐k dielectrics. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 1547–1557 Abstract : Alkylene‐ and arylene‐bridged cyclolinear polycarbosilanes (CLPCS) with 1, 3‐disilacyclobutane (DSCB) rings incorporated in the main chain of the polymer were prepared by polycondensation between corresponding di‐functional DSCB derivatives and di‐Grignard reagents. The phenylene‐bridged CLPCS undergoes photochemically induced crosslinking on UV irradiation to form a thermally stable ( T d (TGA 5%) = 540 °C), crosslinked, polycarbosilane network, solid. The spin‐cast, cured films of these CLPCSs exhibit low dielectric constants and exceptional mechanical properties for applications in electronics, including directly UV‐photopatterned low‐k dielectrics.